Identity Work as Ethical Self-Formation: The Case of Two Chinese English-as-Foreign-Language Teachers in the Context of Curriculum Reform - Jiang, Anne Li (Frontiers in Psychology, 2022)
Curriculum reform urges teachers to constantly reflect on existing identities and develop probably whole new identities. Yet in the wake of the poststructuralist view of identity as a complex matter of the social and the individual, of discourse and practice, and of agency and structure, teacher identity is a process of arguing for themselves and hence ethical and political in nature. Drawing on Foucault’s notion of ethical self-formation and its adoption by Clarke’s (2009a) “Diagram for Doing Identity Work” in teacher education research, this two-year long case study explores how two Chinese English-as-foreign-language (EFL) teachers engaged in identity work in a changing curricular landscape. The analysis of narrative frames and semi-structured interviews reveals the relations between the relative stable and the evolving elements of teachers’ identity work, and the essential role of teachers’ ethical agency based on reflective and critical responsiveness to the contextual reality and the dynamic power relations during the reform. The findings argue for the importance of nourishing teachers’ reflective identity work and ethical agency during the turbulence of educational change.